(untitled) (University Heart Journal, 2013)
Congenital heart disease(CHD) is the most common congenital problem in children. Presentation can vary from asymptomatic , accidental finding to severe cardiac decompensation and death. Early recognition has great implication on prognosis. Our aim was to study age wise distribution and clinical spectrum of Congenital heart disease (CHD) in Bangabandhu Sheikh Mujib Medical University, (BSMMU), Shahbag, Dhaka. A retrospective analysis of 272 patients over a five year period was done. Clinical examination, echocardiography and Colour Doppler was used as diagnostic tools. Ventricular septal defect (VSD) was the common lesion (33.45 %) followed by Atrial septal defect (ASD) in 13.6 % & Patent ductus arteriosus(PDA) in 10.6 %. Tetralogy of Fallot (TOF)was the common cyanotic heart disease (15.8 %). Maximum number of children with heart disease 64% was diagnosed between 0-5 yrs of age. This is a retrospective descriptive study on all patients with the suspected & confirmed diagnosis of congenital heart disease referred for echocardiography over a period of 5 years from October, 2006 to December, 2011. Patients from day one of life till 18 years were included. Study was conducted in the pediatric cardiology dept. of BSMMU, Dhaka. Clinical examination, 2D echocardiography & colour Doppler were considered as definitive tools for diagnosis of congenital heart disease. We received patients from lower to upper middle class strata. We retrospectively analyzed the records of all paediatric first visit OPD (outpatient department) & IPD (Inpatient department) patients between 0-18 years, during the same period. Children diagnosed with CHD were analyzed further. Preterms with PDA were followed up and not included in this study if it is closed spontaneously within the period of hospital stay or by managing conservatively DOI: http://dx.doi.org/10.3329/uhj.v8i2.16064 University Heart Journal Vol. 8, No. 2, July 2012